Teachers readiness in the implementation of teaching reading through the phonics approach in ESL classroom / Nur Azyan Shalihah Mohd Shafee - Mohd Shafee, Nur Azyan Shalihah (2013)
This study aimed to investigate English teachers' readiness in implementing teaching reading through phonics approach as has been outlined in the new KSSR Syllabus. Utilising a quantitative and qualitative research design, 28 English teachers from several schools in Dungun, Terengganu were chosen as respondents for the study. Four research objectives for the study were (i) English teachers' knowledge and understanding on phonics approach, (ii) English teachers' perception on students' knowledge and ability in phonics in the teaching of reading through phonics approach, (iii) English teachers' challenges in teaching reading through phonics approach in early reading and (iv) suggestion in implementing teaching English reading through phonics approach. Two instruments namely Teacher Knowledge Assessment: Structure of Language (TKA:SL) questionnaire adapted from Mather, Bos & Babur (2001) and Teacher Perceptions towards Early Reading and Spelling (TPERS) Deford (1985) were used for the study. In addition, semi-structured interview were conducted in getting further information from the teachers. The findings of the study showed that (i) the teachers have moderate level of knowledge and understanding in teaching reading through phonic approach (ii) it is also revealed that phonological awareness knowledge and spelling skills are important for the emergent readers. Based on the study, it can be concluded that English teachers' knowledge and understanding in teaching reading through phonics approach is inadequate. As phonics approach is something new to them, more time is needed in fully equipped the teachers with useful knowledge, information, skills as well as understanding on the approach.